Pengaruh TATO, DER, ROE, PER terhadap harga saham pada sektor barang konsumsi BEI Tahun 2016-2018 - Natalia, Natalia; Purnasari, Nina; Lumbantoruan, Ratnawaty; Waruwu, Etnasius (Jurnal Paradigma Ekonomika, 2021)
The study was conducted to test how it affects partial independent variables and is simultaneous with bound variables. Where the free variables are Total Asset Turn Over(TATO), Debt To Equity Ratio(DER), Return On Equity(ROE), Price Earning Ratio(PER), and which become variables dependent is the Stock Price. The study had 52 populations while the sample consisted of 34 companies in 3 periods of consumer goods companies, So the total amount of data over three years was 102. In the visible T-Test results, a conclusion can be drawn that partially shows TATO and DER have no effect and no significance to the Stock Price. Where the variables ROE and PER have an influence and significant impact on the Stock Price. Then following the results of the F test, it can be concluded TATO, DER, ROE, and PER there is an influential and significant simultaneous on the Stock Price. The research was tried by the procedure of multiple linear regression methods and the test hypothesis using the Spss 23 process. Â